Digital Health Interventions for the Optimization of Postpartum Cardiovascular Health: A Systematic Scoping Review - Hausvater, Anaïs; Pleasure, Mitchell; Vieira, Dorice; Banco, Darcy; Dodson, John A. (American journal of preventive cardiology, 2025)
Digital health technologies have been proposed as a potential solution to improving maternal cardiovascular (CV) health in the postpartum (PP) period. In this context we performed a systematic scoping review of digital health interventions designed to improve PP CV health. We conducted a systematic review of PubMed/MEDLINE, EMBASE, CINAHL, Web of Science and the Cochrane Library. We included studies of PP women, with an intervention involving digital or mobile health (wearable devices, telemedicine, or remote monitoring). We included studies that measured an outcome related to CV health. 110 full studies were reviewed for eligibility and 38 were included. Studies were categorized into 4 broad CV outcomes: blood pressure (BP), physical activity (PA), diet/weight loss and cardiometabolic markers. Digital health interventions included mobile applications, text-based coaching, interactive websites, virtual reality, wearable devices. The majority of remote BP monitoring programs (N = 5 studies) were successful in optimizing BP. 14 studies examined interventions aimed at improving PA levels of which 6/14 studies showed modest benefit at increasing PA. The majority of interventions aimed at weight loss (N = 27 studies) showed no significant benefit in terms of lowered caloric intake and/or weight loss up to 1 year PP. 6 studies examined improvements in cardiometabolic markers such as lipids and glucose levels, of which the majority showed no benefit. The majority of studies we reviewed found that digital health interventions such as mobile health, telemonitoring and wearable devices were feasible and had mixed effectiveness in improving postpartum CV health in the postpartum period.